Automated Inspection of Pressure Vessels through a Climbing Robot with Sliding Autonomy - Palar, Piatan; Oliveira, André; Terres, Vinícius; Ramos, Julio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
AIR is a climbing robot designed for nondestructive testing and inspection of weld seams in tanks and vessels of the oil and gas industry. In this paper a Fuzzy control system is proposed to a optimal selection of Levels of Autonomy (LoA) at each moment, mixing joystick inputs from an operator and sensor information from the environment to ensure that the movement of tracking weld seams is being achieved while allowing the operator to have full control of the robot's movements without having to control each maneuver manually. Experiments were executed in a simulator environment and are presented along with future ideas for research.